Social Representations of Teachers on Social Media-mediated Formative Assessment - Torres, Danny (Íkala, Revista de Lenguaje y Cultura, 2017)
This research report accounts for teachers’ social representations regarding formative assessment practices by means of social networks. This inquiry aims at building sense of pedagogical implications and reflections of this assessment perspective. Regarding methodological issues, a grounded theory study was accurate under the qualitative research logic; the interpretative nature of this approach allowed to have a full scope of the social reality framed by teachers. Thus, findings suggest representations of different order, accepting and dismissing this inclusion in their teaching practices. Results also evidence the need to reshape a non-instrumental insight of social networks usage, and democratize evaluation tasks online.